Saving Mr. Terupt - Buyea, Rob. (New York : A Yearling Book, 2016)
Mr. Terupt's former students have entered junior high and, each of them having their own personal issues, are afraid their group will split up. Hoping their former teacher can help, they find that it is he who is in need of saving.
Horn Book
School Library Journal
Voice of Youth Advocates (V.O.Y.A.)
Horn Book, April 2016
Kirkus Review, May 2015
School Library Journal, May 2015
Keywords: Junior high school students -- Juvenile fiction; Teacher-student relationships -- Juvenile fiction; Junior high school students -- Fiction; Teacher-student relationships -- Fiction; Junior high school students -- Fiction; Teacher-student relationship -- Fiction